Drug resistance in human immunodeficiency virus type-1 infected Zambian children using adult fixed dose combination stavudine, lamivudine, and nevirapine. - Gupta, R; Ford, D; Mulenga, V; Walker, A; Kabamba, D; Kalumbi, M; Grant, P; Ferrier, A; Pillay, D; Gibb, D; Chintu, C (2010)
BACKGROUND: There are few medium-term virologic data in children from resource-limited settings taking adult fixed-dose-combination antiretroviral therapy (cART) without viral load monitoring. METHODS: CHAP2 (Children with HIV Antibiotic Prophylaxis 2) is a prospective cohort of Zambian children using d4T/3TC/NVP adult Triomune30 dosed according to WHO guidelines. RESULTS: A total of 103 children (19 with previous antiretroviral therapy) had follow-up >6 months. Median age at cART initiation was 8 years (IQR, 6-12) and CD4 8% (4-12). At 24 months, CD4% had increased by a median of 15% (7-25). For 74 children viral load was known/inferred: 51 of 74 (69%) had viral load <50 copies/mL (45 of 63 [71%] with no previous cART, 6 of 11 [55%] with previous cART; difference P = 0.30); 22 of 74 (30%) had viral load >1000 copies/mL. Of 26 children with resistance data, 25 (96%) had NNRTI resistance; 22 (84%) had M184V; 2 (8%) had Q151M; and 1 (4%) each had K65R, L74V, or K70E. Eight (31%) had > or =1 TAM. Those failing virologically with a genotypic sensitivity score of 0 for first-line therapy had a somewhat smaller increase in CD4% from baseline compared with those failing therapy with a genotypic sensitivity score >0 (+3 vs. +8, P = 0.13), and had somewhat lower CD4% at initiation of cART (2 vs. 11, P = 0.09). In 6 children with >1 resistance test, the estimated rate of accumulation of TAMs was 0.59/yr (95% confidence interval: 0.22-1.29). CONCLUSIONS: Twenty-four month virologic responses to cART were good. However, the rate of TAM accumulation in those with rebound was higher than reported in Western adult cohorts, and there was some indication of a detrimental effect of high level resistance on CD4% change from baseline.